2023
DOI: 10.1111/ppl.13946
|View full text |Cite
|
Sign up to set email alerts
|

Boron stimulates fruit formation and reprograms developmental metabolism in sweet cherry

Abstract: Boron modulates a wide range of plant developmental processes; however, the regulation of early fruit development by boron remains poorly defined. We report here the physiological, anatomical, metabolic, and transcriptomic impact of pre‐flowering boron supply on the sweet cherry fruit set and development (S1–S5 stages). Our findings revealed that endogenous boron content increased in early growth stages (S1 and S2 stages) following preflowering boron exogenous application. Boron treatment resulted in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This could be attributed to the fact that while the transcriptional regulation in dormant buds is limited, during the transition from endodormancy to ecodormancy an explosion of transcription activity has been observed that clearly divided the ecodormancy from other dormancy stages in sweet cherries [44][45][46]. Similarly, the early stage of fruit development is characterized by elevated transcriptional activity due to continuous cell division that progressively decreases in the following stages [47,48]. Hence, the endorsement of transcriptional activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the fact that while the transcriptional regulation in dormant buds is limited, during the transition from endodormancy to ecodormancy an explosion of transcription activity has been observed that clearly divided the ecodormancy from other dormancy stages in sweet cherries [44][45][46]. Similarly, the early stage of fruit development is characterized by elevated transcriptional activity due to continuous cell division that progressively decreases in the following stages [47,48]. Hence, the endorsement of transcriptional activity was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In higher plants, fully developed leaves serve as the main supplier of photoassimilates, with additional green organs like fruit peels also contributing to the quality of the fruit. Michailidis et al reported the significant role of boron in sweet cherry metabolism, physiological traits, and fruit developmental changes [40]. Panjikar et al applied 0.2% zinc sulfate and 0.1% boric acid to tomatoes, reducing the fruit cracking rate by 90% [41].…”
Section: Qualitymentioning
confidence: 99%
“…Frozen (−80 • C) ground exo-and meso-carp tissues (0.5 g) of each treatment and cultivar in triplicate (biological replicates) in 48 h after treatments were transferred into 2 mL screw-cap tubes for primary polar metabolite extraction, as previously described with slight modifications [32]. In brief, 1.4 mL pure methanol and 0.1 mL of 1 mg mL −1 adonitol were added and incubated for 10 min at 70 • C. After centrifugation (10,000× g), the supernatant was collected, and 0.75 mL chloroform and 1.5 mL dH 2 O were added.…”
Section: Quantification Of Primary Metabolitesmentioning
confidence: 99%